Deteccion en semillas de clavibacter michiganensis subsp. michiganensis, agente causal del cancer bateriano del tomate - Miguel, A.=700 1 Garcia, A.; Amat, Z.; Perez, I.
(Es, En)
Ilus., 9 ref.
Keywords: LYCOPERSICON ESCULENTUM; CLAVIBACTER MICHIGANENSIS; SEMILLAS; METODOS; DIAGNOSTICO; CUBA; CANCER BACTERIANO